Ketika Watchdog Dipelihara Para Juragan: Kontrol Pengusaha terhadap Media Massa - Putra, I Gusti Ngurah (Jurnal Ilmu Sosial dan Ilmu Politik, 2008)
As a watch dog, Indonesia mass media now are in dangerous situation. They are trapped between whether they should be servant of the public by doing their duty to bark when watching bad practices in any social institution or they should serve the people who support their existence, namely the conglomerates. This is so due to thefact that mass media now depend mostly on advertising revenues and are controlIed by the conglomerates who have interest in making good images in public eyes. This article discusses the tendency of Indonesia media being controlled by conglomerates through various mechanisms.